Compatibilidad de la yuca con cuatro especies silvestres de Manihot de Brasil Central - Nassar, N.M.A (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
Hybridizations between cassava (Yuca), Manibol esculenta Crantz, and the wild species, M anomala Pohl, M. oligantha Pax subsp nesteli, M. gracilis Pax, and M. zehutneri Ule were fertile. Meiosis of the four species was regular, particularly the formation of 18 bivalents in all species. Anaphase I was normal with an equal distribution of 18 chromosomes at each pole. No laggards, delayed separation of bivalents, restitution nuclei, or polyads could be observed. Pollen of the four species was moderately viable.